Persistence of Spatial Memory Induced by Spaced Training Involves a Behavioral-Tagging Process. (10th August 2022) - Correa, J.; Tintorelli, R.; Budriesi, P.; Viola, H.
Graphical abstract: Highlights: Spaced learning induces persistence of spatial object recognition memory. Persistence by spaced learning depends on the mechanism of memory expression. Memory reconsolidation processes are not involved in the spaced learning effect. Promotion of memory persistence involves a behavioral tagging process at retraining. ERKs set the tag and GluA2-containing AMPA receptor is required at relearning. Abstract: Spaced training, which involves long inter-trial intervals, has positive effects on memories. One of the main attributes of long-term memories (LTM) is persistence. Here, to identify the process that promotes LTM persistence by spaced learning, we used the spatial object recognition (SOR) task in rats. The protocol consisted of a first strong training session that induced LTM formation (tested 1 day after training), but not LTM persistence (tested 7 or 14 days after training); and a second weak training session that promoted memory persistence when applied 1 day, but not 7 days, after the first training. We propose that the promotion of memory persistence is based on the Behavioral Tagging (BT) mechanism operating when the memory trace is retrieved. BT involves the setting of a tag induced by learning which gives rise to input selectivity, and the use of plasticity-related proteins (PRPs) to establish the mnemonic trace. We postulate that retraining will mainly retag the sites initially activated by the original learning, where the PRPs needed for memory expression and/or induced by retrieval would be used to maintain a persistent mnemonic trace. Our results suggest that the mechanism of memory expression, but not those of memory reinforcement or reconsolidation, is necessary to promote memory persistence after retraining. The molecular mechanisms involve ERKs1/2 activity to set the SOR learning tag, and the availability of GluA2-containing AMPA receptor. In conclusion, both the synthesis of PRPs and the setting of learning tags are key processes triggered by retraining that allow SOR memory persistence.